Derivatives : - Wilmott, Paul (J. Wiley, 1998)
The book is divided into six parts: Part One: acts as an introduction and explanation of the fundamentals of derivatives theory and practice, dealing with the equity, commodity and currency worlds. Part Two: takes the mathematics of Part One to a more complex level, introducing the concept of path dependency. Part Three: concerns extensions of the Black-Scholes world, both classic and modern. Part Four : deals with models for fixed-income products. Part Five : describes models for risk management and measurement. Part Six : delivers the numerical methods required for implementing the models described in the rest of the book Derivatives also includes a CD containing a wide variety of implementation material related to the book in the form of spreadsheets and executable programs together with resource material such as demonstration software and relevant contributed articles.